THE REVIEW OF WAYS OF UNDERSTANDING IN PROVING CONGRUENCE OF TWO TRIANGLES - Aditya Prihandhika; Nur Azizah (Program Studi Pendidikan Matematika Universitas Muhammadiyah Kuningan, 2024)
This study aims to reviewing ways of understanding of prospective mathematics teacher students in the process of proving the triangle congruence theorem deductively. Deductive proof is a process that is quite difficult to do if students do not know the postulates, theorems, definitions, and properties that can be used as references in the proof process. The mathematical critical thinking process needs to be reviewed to determine the relevance of students' considerations in choosing the various references needed. The study used a case study to investigate the phenomenon specifically. The participants involved in the study were five students from a university in West Java. Theory of ways of understanding is needed to examine students' understanding of postulates, theorems, definitions, and other properties that have been studied previously so that it can be known to what extent students can validate the proof process carried out. The results of the study showed that based on the ways of understanding they have, students can prove the congruence theorem of two triangles by formulating the main problems, expressing facts, choosing logical arguments, detecting information bias with different points of view, and being able to draw conclusions. Thus, in the deductive proof process, a good way of understanding is required regarding postulates, theorems, definitions, and other relevant properties to reach systematic conclusions.